Magnifying endoscopy is useful for tumor border diagnosis in ulcerative colitis patients. Issue 6 (June 2022) - Nishio, Masafumi; Hirasawa, Kingo; Ozeki, Yuichiro; Sawada, Atsushi; Ikeda, Ryosuke; Fukuchi, Takehide; Kobayashi, Ryosuke; Sato, Chiko; Ogashiwa, Tsuyoshi; Inayama, Yoshiaki; Kunisaki, Reiko; Maeda, Shin
Abstract: Background and aims: Endoscopic resection (ER) is feasible for well-circumscribed tumors in patients with ulcerative colitis (UC); however, the specific manner for diagnosis of the tumor border is unclear. We evaluated the efficacy of magnifying endoscopy (ME) for the diagnosis of tumor borders in UC. Methods: We analyzed endoscopically or surgically resected tumors in UC patients in whom both chromoendoscopy (CE) and ME were performed, retrospectively. We classified the tumors based on tumor border visibility and evaluated tumor's characteristics and ER outcomes. Results: We examined 100 tumors from 76 UC patients (66 distinct and 34 indistinct on CE). In 22 (65%) indistinct tumors on CE, ME improved the tumor border visibility. Compared with distinct tumors on CE, nonpolypoid and large tumors were more common in indistinct tumors on CE. In indistinct tumors even on ME, flat or depressed morphologies and type V pit were more frequently than in other groups. Sixty-five distinct tumors on CE and 18 distinct tumors on ME alone were treated endoscopically, and their R0 resection rate were 91% and 95% ( p > 0.99). Conclusions: ME can improve the tumor border visibility in UC, and ER is feasible for tumors whose border can be visualized on ME.